Central African Economic and Monetary Community (CEMAC) : Common Policies of Member Countries, and Common Policies in Support of Member Countries Reform Programs-Press Release; Staff Report; and Statement by the Executive Director. (IMF Staff Country Reports; Country Report, 2019)
The regional strategy has helped to avert an immediate crisis but continues to face headwinds: two countries have yet to enter financing arrangements with the Fund: regional reserves have underperformed despite higher-than-projected oil prices; the projected recovery of non-oil growth has still to materialize; and the security, social, and political context remains challenging. Consistent with the policy assurances it had provided, the BEAC has taken corrective actions, including an increase in its policy rate, to address the NFA underperformance and has made substantial progress toward finalizing by end-year the modernization of the monetary policy operational framework and the drafting of new foreign exchange regulations. A follow-up letter of support provides updated policy assurances on the NFA path. The medium-term outlook continues to see a gradual improvement in the economic and financial situation but is subject to substantial downside risks, including further delays in the approval of financial arrangements with Congo and Equatorial Guinea, lower oil prices, and tighter global financial conditions. The region continues to face daunting challenges to diversify its economy, with a poor business environment and high perception of corruption.